2008
DOI: 10.1177/0022466907313349
|View full text |Cite
|
Sign up to set email alerts
|

Applying Response to Intervention Metrics in the Social Domain for Students at Risk of Developing Emotional or Behavioral Disorders

Abstract: Response to Intervention (RtI) has become an important element of policy, practice, and research since the 2004 reauthorization of the Individuals with Disabilities Education Act. In this article, five metrics recommended by Gresham (2005) were used to evaluate the progress of 127 students who were at risk of developing emotional disturbance and enrolled in a Tier 2 targeted group intervention. Student progress on a daily behavior report card was used to identify responders and nonresponders. Results suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 20 publications
1
83
0
2
Order By: Relevance
“…In one singlesubject study, a functional relation was discussed by authors who indicated one could not be established due to the limitation of the design (i.e., AB design; Swoszowski, Jolivette, & Fredrick, 2013). Statistically significant effects were reported for students' classroom behavior (e.g., Fabiano et al, 2010;Simonsen et al, 2011); daily report cards (e.g., Cheney et al, 2008;Cheney et al, 2009); scores on the Social Skills Rating System (Gresham & Elliott, 1990;e.g., Cheney et al, 2008;Cheney et al, 2009), Teacher Rating Form (Achenbach, 2001; e.g., Cheney et al, 2009), and Behavior Assessment Scale for Children 2 (Reynolds & Kamphaus, 2004;e.g., McIntosh et al, 2009); academic productivity and success (e.g., Fabiano et al, 2010); and office discipline referrals (e.g., Hawken, O'Neill, & MacLeod, 2011;McIntosh et al, 2009).…”
Section: Cico Variationsmentioning
confidence: 99%
“…In one singlesubject study, a functional relation was discussed by authors who indicated one could not be established due to the limitation of the design (i.e., AB design; Swoszowski, Jolivette, & Fredrick, 2013). Statistically significant effects were reported for students' classroom behavior (e.g., Fabiano et al, 2010;Simonsen et al, 2011); daily report cards (e.g., Cheney et al, 2008;Cheney et al, 2009); scores on the Social Skills Rating System (Gresham & Elliott, 1990;e.g., Cheney et al, 2008;Cheney et al, 2009), Teacher Rating Form (Achenbach, 2001; e.g., Cheney et al, 2009), and Behavior Assessment Scale for Children 2 (Reynolds & Kamphaus, 2004;e.g., McIntosh et al, 2009); academic productivity and success (e.g., Fabiano et al, 2010); and office discipline referrals (e.g., Hawken, O'Neill, & MacLeod, 2011;McIntosh et al, 2009).…”
Section: Cico Variationsmentioning
confidence: 99%
“…All six students decreased problem behaviour and increased academic study skills. In a study by Cheney, Flower, and Templeton (2008), two-thirds of 127 students at risk for behaviour problems responded to Tier-2-targeted intervention. The intervention reduced the prevalence of emotional-behaviour disorders by 50%.…”
Section: Effects Of Rti Implementationmentioning
confidence: 99%
“…Tutors and entrepreneurs think that these young people show low self-confidence, low self-esteem, and low motivation, chiefly at the beginning of the training programme. They refer these features as disruptive behaviours as many authors do (Cheney, Flower y Templeton, 2008;Kazdin y Buela, 1994;Carrascosa y Martínez, 1998;Walker et al, 1996). But as these youths progress in the training programme, they improve this behavioural profile and increase their self-confidence, self-esteem, and motivations because they perceive that they are able to achieve the aims of this applied and personalized training programmes.…”
Section: Discussionmentioning
confidence: 99%